Infertility in India: social, religion and cultural influence - Sheoran, Poonam; Sarin, Jyoti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Society, culture and religion frame the major sphere of life for human kind since starting. Fertility has been one of man’s desired attributes since the beginning of recorded history and remains a driving need for young couples today. Infertility, however, continues to be a major worldwide problem, affecting an estimated 60-80 million women and men, a vast majority of whom live in low resource countries. The aim of the study was to assess the living-in experiences of infertile women under social and religional and cultural influence. Methods: This was a phenomenological study conducted at Infertility clinic of Haryana, India. Data was collected was semi structured interview guide and face to face in depth interviews. Participants were selected using criterion sampling technique and data saturation was achieved after 22 interviews. All interviews were audiotaped using a digital recorder. Results: The findings of the study showed that three main themes related to social, religious and cultural influence with core theme of Environmental influence of their infertility experience. Conclusions: The study concluded that there is a huge burden on the part of female to have a baby after marriage. Also the childless women face social and financial adversities at time and this is not limited to low income or low education strata. Health care professionals need to understand cultural and social implications of infertility in order to provide counseling, and referring women with fertility concerns for consultation and further treatment.